Annotation guidelines: heuristics applied while selecting terms for semantic markup from the text of Reis et al. (2008) Impact of environment and social gradient on Leptospira infection in urban slums - Portwin, K; Shotton, D (Image Bioinformatics Research Group, Department of Zoology, 2009)
Semantic markup of the text of the cited PLoS Neglected Tropical Diseases (PLoS NTD) article by Reis et al. (2008) was implemented manually by Katie Portwin and David Shotton, Image Bioinformatics Research Group, Department of Zoology, University of Oxford. The semantically enhanced version of that article was published on 3 September 2008 at doi:10.1371/journal.pntd.0000228.x001, and the paper by Shotton et al. (2009) describes the full range of semantic enhancement applied to that Reis et al. (2008) article. A separate document (Shotton and Portwin, 2009; doi:10.1371/journal.pntd.0000228.x009) describes the technical implementation of those semantic enhancements, while this document describes the heuristics we applied when deciding which textual terms were to be assigned to the semantic classes highlighted in the text of the enhanced version of the article.